Frequency and risk factors for malnutrition in children undergoing general anaesthesia in a French university hospital: A cross-sectional observational study. Issue 8 (August 2017) - Gerbaud-Morlaes, Louis; Frison, Eric; Babre, Florence; De Luca, Arnaud; Didier, Anne; Borde, Maryline; Zaghet, Brigitte; Batoz, Hélène; Semjen, François; Nouette-Gaulain, Karine; Enaud, Raphael; Hankard, Régis; et al.
Abstract : BACKGROUND: Malnutrition is often underdiagnosed in hospitalised children, although it is associated with postoperative complications, longer hospital lengths of stay and increased healthcare-related costs. OBJECTIVE: We aimed to estimate the frequency of, and identify factors associated with, malnutrition in children undergoing anaesthesia. DESIGN: Cross-sectional observational study. SETTING: Paediatric anaesthesia department at the University Children's Hospital, Bordeaux, France. PARTICIPANTS: A total of 985 patients aged less than 18 years. MAIN OUTCOME MEASURES: Anthropometric measurements, American Society of Anesthesiologists physical status classification score and the Pediatric Nutritional Risk Score (PNRS) recorded at the pre-anaesthesia evaluation. RESULTS: When assessed as a Waterlow index less than 80%, malnutrition was present in 7.6% children. This increased to 8.1% of children assessed by clinical signs and to 11% of children when defined by a BMI less than the third percentile. In a univariate analysis, children with a BMI less than the third percentile were more often born prematurely (22.4 vs 10.4%; P = 0.0008), were small for gestational age at birth (18.4 vs 4.5%; P < 0.0001), were admitted from the emergency department (12.0 vs 5.6%; P = 0.02), had a high American Society of Anesthesiologists score ( P < 0.0001), or had a high Pediatric Nutritional Risk Score ( P < 0.0001). Presence ( P = 0.01) and type ( P = 0.002) of chronic disease were also associated with malnutrition. In the multivariate analysis, a premature birth, a lower birth weight and a higher Pediatric Nutritional Risk Score were significantly associated with a higher odds of malnutrition when defined by BMI. CONCLUSION: All children should be screened routinely for malnutrition or the risk of malnutrition at the pre-anaesthesia visit, allowing a programme of preoperative and/or postoperative nutritional support to be initiated. We suggest that as well as weight and height, BMI and a pediatric nutritional risk score such as PNRS should be recorded routinely at the pre-anaesthesia visit.